Inheritance Anomaly of Daughter “Batang Angkola” Based on Islamic Law and Common Law - Syahrini Harahap; Syafruddin Syam; Ramadhan Syahmedi Siregar (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
This study aimed to determine and analyze the distribution of Angkola customary inheritance to daughters. The type of research was field research, with a qualitative descriptive method, and the approach used legal sociology and a state approach. In contrast, the data types used consisted of primary and secondary data. The findings were that the kinship system used by the Angkola tribe in the distribution of inheritance adheres to a patrilineal kinship system, so with this patrilineal system, the position and inheritance rights of daughters are not recognized by Angkola custom. Even though they are not classified as heirs, daughters can still get a share of their parent's inheritance utilizing Olong Ate, namely giving love from a brother to his sister without a nominal amount. With the concept of Olong Ate, the share received by Daughter cannot be determined; the share for Daughter may be less, more, or equal to the share for boys. If Daughter's share is equal to or bigger than the boys, then there is a clash between Angkola customary and Islamic inheritance laws